The effective utilization of construction materials. (2022) - Anitha, R.; Nivedhitha,; Janani, R.; Banupriya, S.
Abstract: All our world Construction industry have major role to providing better life to everyone with respect to the development of nation, road service, transportation ect., meanwhile this industry consume lot of resources and producing waste also. This will affect the environment by carbonization. The awareness about the wastage of materials should mandatory to every person and every industry. This paper deals with percentage of wastage on concrete, reinforcement, and formwork in residential building, commercial building as well as other type of building and the percentage of wastages for the causes of wastages factors are design and documentation, operational wastage, procurement and materials storage and handling.